Proglacial lake development and outburst flood hazard at Fjallsjökull glacier, southeast Iceland - G. H. Wells; G. H. Wells; Þ. Sæmundsson; Þ. Sæmundsson; F. Pálsson; G. Aðalgeirsdóttir; E. Magnússon; R. L. Hermanns; R. L. Hermanns; S. Guðmundsson (Natural Hazards and Earth System Sciences)
Glacier retreat is projected to continue with ongoing climate change, elevating the risk of mass-movement-triggered glacial lake outburst floods (GLOFs). These events are an emerging yet understudied hazard in Iceland, including at Fjallsjökull, an outlet glacier of the Vatnajökull ice cap in southeast Iceland. The proglacial Fjallsárlón lake significantly expanded from 1945 to 2021, enabling measurements of lake depth and volume changes with a multibeam sonar scanner. This lake bathymetry, coupled with radio-echo sounding surveys of subglacial topography, makes it possible to estimate future lake development. If recent glacier terminus retreat rates continue, Fjallsárlón is estimated to reach its maximum extent within the next 1 to 2 centuries, more than doubling in surface area and tripling in volume. The lake will occupy two overdeepened basins with a maximum depth of ∼ 210 m, which will likely increase terminus melting and calving rates – and thus glacier retreat – as well as potentially float the glacier tongue. Three zones on the valley walls above Fjallsjökull have high topographic potential of sourcing rock falls or avalanches that could enter Fjallsárlón and generate displacement waves that could exit the lake as GLOFs, impacting visitors and infrastructure at this popular tourism site. This study offers an assessment of mass-movement-triggered GLOF hazard at Fjallsárlón – the first time this emerging risk has been investigated in Iceland. Results provide high-resolution multibeam sonar measurements of lake bathymetry that can inform additional studies on glacier–lake interactions, GLOF risk mitigation strategies, and selection of priority sites for monitoring and additional mapping at Fjallsárlón, with potential application to other proglacial regions worldwide.